Carpological characters of the species of the Cephalaria (Dipsacaceae) in the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The micro- and macromorphological characters of the fruits within genus Cephalaria in the flora of Ukraine are given. The structural peculiarities of the fruits were clarified and their detailed characteristics were presented. The fruit shape of Cephalaria is tetrahedral, elongated, ribbed, furrowed at the top. There are epicalyx on the top ends with teeth, the length of which from 100 μm (C. coriacea) to 600–800 μm (C. uralensis). The properly cup is on the short stem on the top of the fruit, densely pubescent and bristly. The differences in the microstructure of the surface were established. C. transsylvanica and C. uralensis has gibbous-ribbed surfaces microstructure, C. coriacea has pitted-ribbed, while C. demetrii has a wrinkled-gibbous surface. The fruits are uniformly densely pubescent in all studied species, except of C. coriacea with sparsely pubescent fruits. The pubescence is represented by simple (rigid and soft) and glandular hairs. The shape of the simple hairs are tubular, with a pointed tip, but C. demetrii and C. coriacea have a ribbon-like hairs. The simple hairs have a convex expanded or spherical base, with short tapered legs. Cephalaria transsylvanica differ from other species by a larger spherical hair base. Two morphologically distinct types (warty and smooth) of the microstructure surface on simple hairs were revealed. The glandular hairs are 1–2-celled, with spherical heads, but sometimes C. demetrii has elongated heads. The surface microstructure, localization and density of fruit pubescence, structural features of simple hairs are important carpological characters that we propose to use for precise determination of the species.
Keywords: fruits, micro- and macromorphological characters, pubescence, simple and glandular hairs, surface microstructure.